Leadership Approaches and Job Satisfaction at Chemelil Sugar Company Limited Kenya - Ochieng, Boaz Otieno; Moturi, Damaris Moturi (Human Resource and Leadership Journal, 2025)
Purpose: The study aimed at investigating the influence of leadership approaches on job satisfaction in public sector in Kenya with specific case reference of Chemelil Sugar Company Limited. Methodology: A case study research design was used. The target population of 861 employees of Chemelil Sugar Company was adopted. A sample of 83 employees was selected using a stratified random sampling technique. The data was collected using questionnaires. Data analysis was conducted using frequencies, percentages, Pearson correlation and logistic regression. Findings: The Pearson product moment correlation revealed the relationship between management approaches and job satisfaction as follows: authoritative negatively impacted on satisfaction (r = -0.235), affiliative strongly positively impacted satisfaction (r= 0.727, p < 0.05)., democratic very strongly impacted satisfaction (r= 0.984, p < 0.05). and bureaucratic negatively impacted on satisfaction (r= -.436). Unique Contribution to Theory Practice and Policy: The study recommended that for the job satisfaction to improve in this company, all the leadership approaches should be applied at balanced levels.